Initial Clinical Experience with a New Biointegrative Cement for Vertebroplasty in Osteoporotic Vertebral Fractures - Siemund, R. (Centauro S.r.l., 2009)
Polymethylmethacrylate, as a widely used material for vertebroplasty, has several drawbacks such as heat development and high allergenic potential. In order to avoid these drawbacks ceramic cement materials have been developed. The purpose of this study was to evaluate a new biointegrative material for vertebroplasty in osteoporotic vertebral fractures regarding pain relief, safety aspects and technical feasibility. The injectable bone substitute Cerament™ SpineSupport has been developed for vertebroplasty of osteoporotic vertebral fractures. The aim of the product is to provide mechanical stability by cured calcium sulfate dehydrate during a period of several weeks and to act as an osteoconductive support by hydroxyl apatite particles. Inclusion criteria were a stable single vertebral fracture at levels Th5 to L5, verified by CT and MRI, and not older than four weeks, in osteoporotic patients aged 60 years or older. Bipedicular vertebroplasty technique was used. Follow up included CT directly after treatment and after two month and pain assessment (VAS) pre and post procedure after two weeks and one month. Seven patients (age range 62-96 years, mean 73.9, five women, two men) were treated at levels T 8 (n=1), T12 (n=4) and L1 (n=2). The average injected volume was 1.9 ml (range 0.2-4 ml). No material or procedure-related complications were observed. An average height loss of the treated vertebral bodies of 3.6 mm (range 1.5-5.4) was seen two months after treatment as compared to pre-treatment CT. Pain assessment by VAS resulted in an improvement from mean 69 prior treatment to 37 the day post treatment, 42 after two weeks and 30 after one month. Initial results indicate that Cerament™ Spine Support is safe and effective in the treatment of acute osteoporotic vertebral body fractures. Further studies with long-term follow-up are needed to confirm these results and to prove the concept of osteoconduction with hydroxyl apatite particles.